“State of Exception”: A Tool for Fighting Terrorism - Apatinga, Gervin Ane (2017)
This paper examines Giorgio Agamben’s work on the state of exception, a top-down approach in which the sovereign suspends the constitutional law and imposes decisions on subjects through exceptional mechanisms. The paper seeks to tease out the analytical merit of the concept in helping to interpret the rise of emergency regimes in the current epoch. The paper analyzes some recent cases in France and the United States involving exceptional policies to elucidate the worthiness of Agamben’s work on exceptionalism. Keywords: state of exception, bare life, sovereign ban, terrorism, governmen